Teaching, learning and visual literacy : the dual role of visual representations - Eilam, Billie , 1946- (Cambridge University Press, 2012)
"Visual literacy is an increasingly critical skill in a globalizing, digital world. This book addresses the core issues concerning visual literacy in education, underscoring its importance for the instruction of students and educators. Professor Billie Eilam argues that the incorporation of visual skill development in teacher training programs will help break the cycle of visual illiteracy. Understanding the pedagogical benefits and risks of visual representation can help educators develop effective strategies to produce visually literate students. Eilam presents a broad overview of theoretical knowledge regarding visual representation, as well as a discussion of best practices for the use of visual elements in schools. In addition to theory, Eilam includes practical exercises for introducing visual literacy into teacher education, offering strategies for analyzing visualization in curricula and for increasing awareness of visual culture"-- Provided by publisher